Communicating corporate responsibility through media. (1st April 2010) - Kujala, Johanna; Toikka, Tiina; Heikkinen, Anna
The purpose of this study is to analyse 'how a company communicates its corporate responsibility activities through press releases' and 'how these activities are then presented by media in newspaper articles'. Our analysis is targeted at an empirical case of building a pulp mill in Uruguay. The data consist of the company's press releases and of the newspaper articles published in the biggest quality daily in Finland related to the construction project. The data analysis is conducted as a qualitative content analysis. Corporate responsibility activities are identified utilising the three dimensions of corporate responsibility. In addition, the most important stakeholders are identified and the elements of firm-stakeholder relations analysed. Our findings suggest that in terms of the three dimensions of corporate responsibility the company provided more information than what the media presented to its audience. On the other hand, the newspaper articles consisted of much more information than the press releases regarding the stakeholder relationships.